2006
DOI: 10.1161/01.res.0000217283.98806.a6
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Hypertension in Rats Transduced With CYP4A2 Adenovirus

Abstract: Abstract-Vascular cytochrome P450 (CYP) 4A enzymes catalyze the synthesis of 20-hydroxyeicosatetraenoic acid (20-HETE), an eicosanoid which participates in the regulation of vascular tone by sensitizing the smooth muscle cells to constrictor and myogenic stimuli. This study was undertaken to investigate the consequences of CYP4A overexpression on blood pressure and endothelial function in rats treated with adenoviral vectors carrying the CYP4A2 construct. Intravenous injection of Adv-CYP4A2 increased blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 59 publications
(59 reference statements)
9
115
0
Order By: Relevance
“…At day 14, rats were anesthetized with phenobarbital (50 mg/kg of body weight); kidneys were perfused in situ, and renal interlobar arteries were microdissected as described. 13 …”
Section: Animal Experimentationmentioning
confidence: 99%
See 3 more Smart Citations
“…At day 14, rats were anesthetized with phenobarbital (50 mg/kg of body weight); kidneys were perfused in situ, and renal interlobar arteries were microdissected as described. 13 …”
Section: Animal Experimentationmentioning
confidence: 99%
“…Western blot analysis of arterial segments was performed as described previously 13 using the following primary antibodies: CYP 4A1 polyclonal antibody (Daiichi Chemical Co); nitrotyrosine polyclonal antibody (Cayman Chemicals), gp91 phox and p47 phox polyclonal antibodies (Upstate Co), and endothelial NO synthase (eNOS) polyclonal antibody (Santa Cruz Biotechnology).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that 20-HETE acts as a potent vasoconstrictor of cerebral microvessels (Harder et al, 1994), and has an important role in the autoregulation of cerebral blood flow (Gebremedhin et al, 2000). 20-Hydroxyeicosatetraenoic acid has also been reported to induce the formation of oxygen radicals by interacting with nicotinamide adenine dinucleotide phosphate-oxidase and nitric oxide synthase (Wang et al, 2006;Cheng et al, 2008;Medhora et al, 2008). Previously, we reported that brain and plasma 20-HETE levels were significantly increased in the rat transient middle cerebral artery occlusion (tMCAO) model (Tanaka et al, 2007), and inhibition of 20-HETE synthesis by N-(3-chloro-4-morpholin-4-yl)phenyl-N'-hydroxyimido formamide (TS-011), a selective inhibitor of CYP4s, improved the autoregulatory dysfunction in the peri-infarct microcirculation and the neurologic outcomes in rat and monkey stroke models by reducing the infarct volume of the brain after ischemia (Miyata et al, 2005;Omura et al, 2006;Tanaka et al, 2007;Marumo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%